Translating activism. Activism in translation. Life Scotland for LGBT Young People from English to Italian - Melchiorre, Sonia Maria (Traduttologia e Traduzioni, vol. III: Interdisciplinarietà della traduzione, 2021)
The term activism usually refers to an activity aimed to produce some change at political and/or social level. An activist translation consists therefore in the practice which, through the means of translation, has this precise objective. If on the one hand the tool of translation can help reaching the objective, on the other the very selection of the texts chosen for the translation can also imply a precise ideal audience in the mind of the translator. The translation of a text can therefore help produce cultural change, which has now come to be identified as the performative aspect of activist translation. The present contribution focuses on one particular document published in 2017 in Scotland concerning the introduction of the LGBT+ history in the national educational curriculum to help fight gender-based discrimination and bullying.